2021
DOI: 10.7759/cureus.18573
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Newborn Infants Delivered to Pregnant Women With Laboratory-Confirmed COVID-19: A Single-Center Experience From Saudi Arabia

Abstract: IntroductionIn Saudi Arabia and countries around the world, clinical health practice has been transformed by the coronavirus 2019 (COVID-19) pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). During the early days of the pandemic, it was a major challenge to care for pregnant women with laboratory-confirmed COVID-19 and their newborn infants. In this article, we share our experience in the management of newborn infants delivered to mothers with laboratory-confirmed COVID-19. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…All studies included infants born through vaginal and cesarean sections. In 14 studies the mother-infant dyad was enabled to stay together after birth 24 h a day 13 , 14 , 18 , 19 , 21 , 23 27 , 29 , 31 , 32 , 36 , in 6 it was not allowed 17 , 20 , 28 , 30 , 33 , 33 and in the remaining 6 studies 15 , 16 , 22 , 35 , 37 , 38 , there was no information about it. In 12 studies two or more preventive measures were undertaken 14 , 17 , 19 , 21 , 23 , 26 , 27 , 29 31 , 33 , 34 , in 10 only one or no one 13 , 15 , 16 , 18 , 20 , 22 , 24 , 25 , 28 , 36 and in the remaining 4 studies there was no information about preventive measures 32 , 35 , 37 , 38 .…”
Section: Resultsmentioning
confidence: 99%
“…All studies included infants born through vaginal and cesarean sections. In 14 studies the mother-infant dyad was enabled to stay together after birth 24 h a day 13 , 14 , 18 , 19 , 21 , 23 27 , 29 , 31 , 32 , 36 , in 6 it was not allowed 17 , 20 , 28 , 30 , 33 , 33 and in the remaining 6 studies 15 , 16 , 22 , 35 , 37 , 38 , there was no information about it. In 12 studies two or more preventive measures were undertaken 14 , 17 , 19 , 21 , 23 , 26 , 27 , 29 31 , 33 , 34 , in 10 only one or no one 13 , 15 , 16 , 18 , 20 , 22 , 24 , 25 , 28 , 36 and in the remaining 4 studies there was no information about preventive measures 32 , 35 , 37 , 38 .…”
Section: Resultsmentioning
confidence: 99%
“…The low mortality rate and ICU admission reported from Iran and KSA are similar to the one observed in several studies worldwide conducted on pregnant women infected with SARS-CoV-2 ( Allotey et al, 2020 ; Elshafeey et al, 2020 ; Juan et al, 2020 ; Smith et al, 2020 ). In pregnant women with COVID-19 in this country, vaginal delivery was more prevalent than the cesarian one ( Algadeeb et al, 2020 ; Alhamoud et al, 2020 ; Al-Matary et al, 2021 ; AlQurashi et al, 2021 ). The most frequent adverse pregnancy outcomes were premature followed by fetal distress, and preeclampsia which occurred in pregnant women <37 weeks of gestational age ( Al-Matary et al, 2021 ).…”
Section: Pregnant Women and Neonatesmentioning
confidence: 89%
“…One study found that the most common symptoms were cough, fever, and dyspnea ( Al-Matary et al, 2021 ). The majority of infected pregnant women did not have comorbidities and experienced a mild or moderate disease ( Alhamoud et al, 2020 ; Al-Matary et al, 2021 ; AlQurashi et al, 2021 ). A small proportion only, required intensive care and respiratory support as they developed symptoms of pneumonia; this finding was reported in pregnant women between 26 and 36 weeks of gestational age ( Al-Matary et al, 2021 ).…”
Section: Pregnant Women and Neonatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Os demais estudos revisados (evidências 2, 3, 4, 10, 11, 16, 17 e 18) demonstram condutas negativas no que diz respeito às ações referentes tanto à amamentação a respeito do contato pele a pele e separação das mães e dos bebês, entretanto, em alguns estudos, verificou-se que a coleta de dados foi feita antes da publicação em Junho das recomendações da OMS (2020) que orientam a manutenção do aleitamento materno e contato pele a pele em mães e neonatos confirmados ou suspeitos com COVID-19, além de indicar também o alojamento conjunto para a díade (Neo-COVID-19 Research Group, 2021;Gabriel et al 2020;Gonçalves-Ferri et al, 2021;Conti et al, 2021;Farghaly, Kupferman, Castillo, Kim, 2020;Wróblewska-Seniuk, et al, 2021;Zaharie, Hasmasanu, Muresan, Kovacs, Matyas, 2021;AlQurashi et al, 2021).…”
Section: Discussionunclassified